The usefulness of coronary artery calcium score to rule out obstructive coronary artery disease before transcatheter aortic valve replacement. (25th November 2020) - Natanzon, S.S; Mazin, I; Barbash, I; Segev, A; Guetta, V; Konen, E; Goitein, O; Fardman, A; Brodov, Y
Abstract: Introduction: Coronary clearance in patients undergoing TAVR is performed by invasive coronary angiography (ICA) or computed tomography angiography (CTA). We aimed to investigate whether CTA-derived low coronary calcium (CAC) score may rule out obstructive coronary artery disease (CAD) in these patients. Methods: We included 232 consecutive patients with severe aortic stenosis (mean age 80±8; 50% female) who underwent both pre-TAVR CTA and ICA between 2012–2019. Obstructive CAD was defined as a >50% in left main or >70% in the 3 main epicardial vessels. Patients with prior coronary stents or bypass grafts were excluded. CAC score was calculated by Agatston method. Receiver operating characteristic (ROC) was applied to establish the CAC threshold for obstructive CAD, and adjustment for age, gender, diabetes and renal failure was applied. Results: CAC scores range was 3.5–5200 (median = 1028). Eighty-eight patients (38%) had obstructive CAD. ROC curves showed high negative predictive value (NPV) for LAD - CAC score 280, NPV 95%; LCX - CAC score 320, NPV 93%; and RCA - CAC score 347, NPV 90% (figure). Binary logistic regression confirmed CAC score cutoffs per vessel as an independent predictor of obstructive CAD [LAD (OR 3.9, CI 1.1–14, p-0.033); CX (OR 5.7, CI 2.4–12, p<0.001); RCA (OR-5.6, CI 2.5–12, p<0.001)]. Conclusion: CAC score per-vessel can be useful to rule out obstructive CAD in patients with severe aortic stenosis undergoing TAVR. Using specific CAC cut offs can identify patients who may omit ICA Funding Acknowledgement: Type of funding source: None